SIFAT KIMIA DAN FISIK BAHAN UTAMA CONBLOCK RINGAN YANG MENGGUNAKAN AGREGAT SEKAM PADI - . Bakri (PERENNIAL, 2012)
This research aimed to assess the properties of main substances used to produce lightweight composite cement using rice husk as aggregate. Main substances used in this research consisted of Portland cement tipe I, lime, rice husk and rice husk ash. Portland cement tipe I, lime and rice husk obtained from local producers in Makassar, while rice husk ash obtained by burning rice husk conventionally in kiln drum and subsequently followed by burning in furnace of 1400 Barnsted Thermolyne Type at temperature 600 oC for 2 hours. Chemical Content of the substances analyzed by adopted the analysis procedure in SNI 15-2049-2004. Alkalinity of Portland cement tipe I, silica of rice husk ash and Na2O dan K2O was categorized as low, while rice husk was categorized as reactive substance. Key words: Portland cement tipe I, rick husk, rice husk ash, lime, lightweight composite cement